ANALYSIS OF LEARNING RESULTS OF STUDENTS IN THE APPLICATION OF GAMIFICATION QUIZIZZ ON MATHEMATICS LESSONS - Setiawan, Adrianus Danang; Lisnani, Lisnani (PROGRES PENDIDIKAN, 2024)
Gamification is becoming a trend where learning activities will be more fun by playing games, one of which is by using quizizz. In this research, the researcher aims to determine the analysis of student learning outcomes in the application of media quizizz in learning mathematics, especially fractions. The type of research used in this research is qualitative research with a description method. The population used in this research was all 11 grade IV students at Bethesda Elementary School. Data collection techniques are carried out through interviews and analyzing the data that has been obtained. Based on the research results obtained through utilization quizizz In mathematics learning activities regarding fractions, it was found that the learning outcomes of class IV students increased, due to the use of media quizizz. It can increase student motivation in learning and student interest so that it will influence student learning outcomes. Through the results of this research, it is hoped that every school will be able to utilize its quizizz to improve student learning outcomes, especially in fraction material.